2011
DOI: 10.1186/1479-5876-9-164
|View full text |Cite
|
Sign up to set email alerts
|

Replication efficiency of oncolytic vaccinia virus in cell cultures prognosticates the virulence and antitumor efficacy in mice

Abstract: BackgroundWe have shown that insertion of the three vaccinia virus (VACV) promoter-driven foreign gene expression cassettes encoding Renilla luciferase-Aequorea GFP fusion protein, β-galactosidase, and β-glucuronidase into the F14.5L, J2R, and A56R loci of the VACV LIVP genome, respectively, results in a highly attenuated mutant strain GLV-1h68. This strain shows tumor-specific replication and is capable of eradicating tumors with little or no virulence in mice. This study aimed to distinguish the contribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
22
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…As expected, readministration of doxycycline at days 9 and 12 postvirus injection resulted in reinduction of luciferase activity. Moreover, we determined the virus titer at the end of the experiment (13 days postinfection [dpi]) to investigate whether we would be able to detect differences in viral replication, since it has previously been shown that the fewer heterogenous proteins that are expressed, the higher the replication rate is (25). Here, we could not see significant differences between the different virus strains, and the amounts of virus seen with the different groups were similar (Fig.…”
Section: Resultsmentioning
confidence: 70%
“…As expected, readministration of doxycycline at days 9 and 12 postvirus injection resulted in reinduction of luciferase activity. Moreover, we determined the virus titer at the end of the experiment (13 days postinfection [dpi]) to investigate whether we would be able to detect differences in viral replication, since it has previously been shown that the fewer heterogenous proteins that are expressed, the higher the replication rate is (25). Here, we could not see significant differences between the different virus strains, and the amounts of virus seen with the different groups were similar (Fig.…”
Section: Resultsmentioning
confidence: 70%
“…Worschech et al demonstrated several pathways also common in our study including interferon, IL-6, JAK/STAT, PTEN, and ERK/MAPK signaling. 25 Only purine metabolism was a common pathway with Reinboth et al 's study. 26 Like Worschech et al, most of our postinfection cellular gene changes reflected a downregulation and shut down of cellular metabolism.…”
mentioning
confidence: 83%
“…26 Like Worschech et al, most of our postinfection cellular gene changes reflected a downregulation and shut down of cellular metabolism. 25 It is difficult to directly compare changes in gene expression due to RNA isolation from tissue rather than cells, adding the variable of the host immune response and gene expression changes which cannot be assessed in cell culture.…”
mentioning
confidence: 99%
“…In addition, it was found recently that removal of each of the expression cassettes from GLV-1h68 resulted in enhanced virus replication and virulence in mice. The increase in virus replication efficiency was proportionate to the strength of removed VACV promoters linked to foreign genes (Chen et al, 2011).…”
mentioning
confidence: 99%
“…Three isolates that showed natural attenuations due to point mutations and deletions were picked for further analysis, namely LIVP 1.1.1, LIVP 5.1.1, and LIVP 6.1.1. The generation of the recombinant VACV strains GLV-1h70, GLV-1h71, GLV-1h72, GLV-1h73, and GLV-1h74 was described previously (Chen et al, 2011).…”
mentioning
confidence: 99%